AT Genotype of FTO rs9939609 Enhances Risk for Central Obesity Under Obesogenic Lifestyle - Maharani, Citra; Puspasari, Anggelia; Enis, Rina Nofri; Ekaputri, Tia Wida; Shafira, Nyimas Natasha Ayu (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2025)
Background: Central obesity is a major risk factor for cardiovascular diseases, influenced by both genetic and lifestyle factors. The rs9939609 variant of Fat Mass and Obesity-Associated (FTO) gene has been associated with increased risk of central obesity, potentially modulated by dietary intake and physical activity. Objective: This study aimed to investigate the association between the FTO rs9939609 variant and central obesity, and its interaction with dietary intake and physical activity among adults in Jambi, Indonesia. Method: A cross-sectional study was conducted on 175 adults. Central obesity was defined using NCEP ATP III criteria. Dietary intake and physical activity were assessed using 24-hour food recall and the IPAQ, respectively. Genotyping was performed using the Tetra ARMS-PCR. Bivariate analysis was used to assess associations. Results: Individuals with the AT genotype had a significantly increased risk of central obesity (OR= 3.29; 95% CI: 1.30–8.35; p= 0.01). Under the dominant model (AAAT), the association remained significant (OR= 2.90; 95% CI: 1.17-7.16; p= 0.02). The risk was higher among individuals with high caloric intake (OR= 4.64) and low to moderate physical activity (OR= 4.77). Conclusion: The FTO rs9939609 variant is associated with increased central obesity risk, and in the presence of obesogenic lifestyle factors.